KOMPOSISI SPESIES DAN DOMINASI NYAMUK CULEX DI DAERAH ENDEMIS FILARIASIS LIMFATIK DI KELURAHAN PABEAN KOTA PEKALONGAN - Tri Ramadhani (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2009)
Filariasis is one of the communicable disease which is caused by infestation of Filaria worm. The disease is transmitted by various mosquitoes. Pabean village was one of the endemic area in Pekalongan city with lymphatic filariasis problem (microfilariae rate > 1 %). The research aimed to get species and dominan potencial vector filariasis and breeding place.The reseach was an observational study which used cross sectional design . The activity were mosquitoes, larve dipper and pupa collection from August until December 2007. The mosquitoes collection was done twice a week by landing collection and light trap with dry ice.The result showed that the species culex mosquitoes found 19.229, consisted of four species that is Cx.quinquefasciatus,Cx.bitaeniorhynchus,Cx.tritaeniorhynchus, and Cx.vishnui. Mosquito of Cx.quinquefasciatus most dominantly found at all of way of arrest and known as mosquito of vector potential of lymphatic filariasis in Pabean village. Especial breeding place of Cx.quinquefasciatus is water polution and very bad sanitation. The larval density was more than 100 of dipper.